Enhanced Metabolic Potentials and Functional Gene Interactions of Microbial Stress Responses to a 4,100-m Elevational Increase in Freshwater Lakes - Li, Huabing; Zeng, Jin; Ren, Lijuan; Yan, Qingyun; Wu, Qinglong L. (Frontiers in Microbiology, 2021)
Elevation has strong influence on microbial community composition, but its influence on microbial functional genes remains unclear in the aquatic ecosystem. In this study, the functional gene structure of microbes in two lakes at low elevation (ca. 530 meters) and two lakes at high elevation (ca. 4,600 meters) were examined using a comprehensive functional gene array GeoChip 5.0. Microbial functional composition, but not functional gene richness, was significantly different between the low- and high-elevation lakes. The greatest difference was that microbial communities from high-elevation lakes were enriched in functional genes of stress responses, including cold shock, oxygen limitation, osmotic stress, nitrogen limitation, phosphate limitation, glucose limitation, radiation stress, heat shock, protein stress, and sigma factor genes compared with microbial communities from the low-elevation lakes. Higher metabolic potentials were also observed in the degradation of aromatic compounds, chitin, cellulose, and hemicellulose at higher elevations. There was only one phytate degradation gene and one nitrate reduction gene were enriched in the high-elevation lakes. Furthermore, the enhanced interactions and complexity among the co-occurring functional genes in microbial communities of lakes at high elevations were revealed in terms of network size, links, connectivity, and clustering coefficients, and there were more functional genes of stress responses mediating the module hub of this network. The findings of this study highlight the well-developed functional strategies utilized by aquatic microbial communities to withstand the harsh conditions at high elevations.